-2j-20=8j

Simple and best practice solution for -2j-20=8j equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2j-20=8j equation:


Simplifying
-2j + -20 = 8j

Reorder the terms:
-20 + -2j = 8j

Solving
-20 + -2j = 8j

Solving for variable 'j'.

Move all terms containing j to the left, all other terms to the right.

Add '-8j' to each side of the equation.
-20 + -2j + -8j = 8j + -8j

Combine like terms: -2j + -8j = -10j
-20 + -10j = 8j + -8j

Combine like terms: 8j + -8j = 0
-20 + -10j = 0

Add '20' to each side of the equation.
-20 + 20 + -10j = 0 + 20

Combine like terms: -20 + 20 = 0
0 + -10j = 0 + 20
-10j = 0 + 20

Combine like terms: 0 + 20 = 20
-10j = 20

Divide each side by '-10'.
j = -2

Simplifying
j = -2

See similar equations:

| 8z=122 | | 65+90+5x=180 | | -3-y-X=0 | | 2x-8=-8x-24 | | 2(4-9w)= | | 57+51+9x=180 | | 6(-2y-16)-2y=-12 | | 6p+b=144 | | -18s+10=-17s | | (X+18)=(x+10) | | 18x-12=17x-2 | | 0=-x+5y | | 3(2z)=-3 | | -690=10(-7x+22) | | 5x-9x+3=17 | | 8x-4(-3+2)=-12 | | 2m+6n-9(5m-4n)= | | (2x-8)(2x-8)=44 | | 12x+15y=90 | | 100-66=31y-35y | | 10=-x+2y | | 2x-18=9x+6 | | 7.57x+22.71=45.42 | | 5+3t-3=8t+14-3t | | (X+14)=(x-20) | | 25=2(x+3) | | 2x+2(x-28)=-104 | | 2x-1-x=9x-3 | | -18+10=-17s | | (x+4)(x-4)=4 | | 5+y=0.0024x | | 3x+2(x-28)=-104 |

Equations solver categories